Rural women lifestyles: lessons from Nigeria (2009)
Rural women's involvement in family life, social and economic development is growing following efforts to empower them. Efforts of foreign donor agencies, federal and state governments to ensure household food security and reduce poverty have been to establish development initiatives that will ensure rural women's full participation in development. However, most development activities have recorded low rural women's participation. The response of the research community to this low participation of rural women in development activities calls for the documentation of their social and economic activities. This will increase their participation in development activities and enhance gender mainstreaming in the development process. Also, major development initiatives have failed to recognise variations that exist in rural women situations. This study therefore, investigated the lifestyles of rural women in Nigeria using a cross sectional survey. Results indicated that the women surveyed are mostly married, have average age and family size, low education, poor income base and practice a mix of religions. Also results indicated choices, modes and preference in their activities. These are all important variables, which will guide planning and execution of development initiatives and activities and appropriate technologies for rural women in Nigeria.